Perceptions of e- marketing, social media, individuals and purchase intention – what can we learn from research? - Norshidah, Mohamed
Social media began as a tool for people to communicate, engage socially and play. Although the enthusiasm in social media initially began with the younger age group, the interest has expanded to others as well. In the last two or three years, the role of social media has given rise to social commerce phenomenon. It has been pervasively associated as electronic marketing (e-marketing). Besides, it has been regarded as a powerful tool to enhance brand presence. Examples of social media presence at Websites include “visit us on Facebook” or “Follow us on Twitter”. In the next five years, retailers may expect further explosive growth of social media contributed through users’ use and view. Given the notion that social media has been the subject of much zeal to both researchers and practitioners, the research undertakes to examine the contexts of e-marketing perceptions and individuals’ characteristics in the context of social media. This in turn clarifies the e-marketing perceptions and aspects of individuals’ characteristics. Built on prior literature, the present research proposed, developed, tested and validated a theoretical model to explain purchase intention at social media. The results and implications for researchers and practice are discussed herein.